A211 SPONTANEOUS HBV REMISSION AFTER HBV REACTIVATION FOLLOWING TREATMENT WITH SOFOSBUVIR AND VELPATASVIR IN A PATIENT WITH HCV AND HBV CO-INFECTION: CASE REPORT. (4th March 2021) - Chiang, A; Tsoi, K
Abstract: Background: In co-infected patients with hepatitis B (HBV) and hepatitis C (HCV), the treatment of HCV with direct-acting antiviral agents (DAA) can cause HBV reactivation. However, there are no clear guidelines on the timing of treatment initiation, especially in the absence of clinical signs of flare. Aims: Here we discuss the case of a 34-year-old female with HBV and HCV genotype 3 who had HBV reactivation following HCV treatment, but did not require nucleos(t)ide therapy. Methods: She initially presented with chronic inactive hepatitis B and chronic hepatitis C with HBV DNA level of 67.5 IU/mL and HCV RNA level of 3.33 x 10 6 IU/mL. She completed a 12 week course of sofosbuvir and velpatasvir for HCV and achieved sustained virologic remission, but subsequently developed reactivation of her HBV with HBV DNA peaking at 3.41 x 10 4 IU/mL twelve weeks post-treatment. She did not develop any signs of hepatitis and a decision was made to monitor her clinically. Results: Two years later, she spontaneously went into remission with her HBV DNA levels being <10 IU/mL. Conclusions: The significance of this case is to illustrate HBV reactivation following treatment of HCV with DAAs may not necessitate immediate treatment, especially if there are no signs of flare. There have been similar reported cases, but larger prospective studies are required to determine the appropriate clinical context where monitoring may be acceptable instead of immediate treatment. Funding Agencies: None